2006
DOI: 10.1117/12.644595
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing viewing distances in subjective assessment of mobile video

Abstract: The perceptual quality of mobile video is affected by many factors, including codec selection, compression rate, network performance and device characteristics. Given the options associated with generating and transmitting mobile video, there is an industry requirement for video quality measurement tools to ensure that the best achievable quality is delivered to customers. International standards bodies are now considering alternative multimedia perceptual quality methods for mobile video. In order to fairly e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The chosen viewing distance follows the guidelines set-up by VQEG [24] as well as ITU-T Recommendation P.910 [19]. Brotherton et al examined the effect of viewing distance in subjective quality assessment of low-resolution video [25]. In their study, two laboratories conducted two experiments with QCIF videos and one with CIF videos.…”
Section: Methodsmentioning
confidence: 99%
“…The chosen viewing distance follows the guidelines set-up by VQEG [24] as well as ITU-T Recommendation P.910 [19]. Brotherton et al examined the effect of viewing distance in subjective quality assessment of low-resolution video [25]. In their study, two laboratories conducted two experiments with QCIF videos and one with CIF videos.…”
Section: Methodsmentioning
confidence: 99%
“…Based on this and results from a study that specifically looked at the impact on video quality whether the head movements where controlled or not, which concluded that it did not affect the result in a significant way, see Ref. 13. The head-and-chin rest was not used in this part of the test.…”
Section: Experiments 1amentioning
confidence: 99%